Chief Medical Officers` perceptions of barriers and enablers to implementing elite athlete cardiac screening programs - Davis, A.; Driscoll, T.; Orchard, J.; Orchard, J. (Journal of Science and Medicine in Sport, 2024)
Introduction: Cardiac screening of elite athletes for conditions associated with sudden cardiac arrest/death (SCA/D) is recommended by national and international guidelines, including the Australasian College of Sport and Exercise Physicians (ACSEP) position statement. Chief medical officers (CMOs) of sporting organisations are generally responsible for implementing the cardiac screening program. The aim of this study was to investigate CMOs` perceptions of barriers and enablers to implementation of cardiac screening in their sporting organisation. Methods: Ten semi-structured interviews were conducted via videoconference from June 2023 to April 2024. Participants were Sport and Exercise Physicians and CMOs of elite sporting organisations across Australia and New Zealand which have an existing cardiac screening program. Interview questions were focused on logistics, usefulness, and perceptions of cardiac screening in their organisation. Interviews were recorded, transcribed verbatim, and thematically analysed. Results: Two principal enablers to implementation of cardiac screening were identified: 1) Having strong sports cardiology infrastructure improved confidence in both the screening and adequate follow-up of athletes; and 2) Organisational support for cardiac screening reduced administrative load on medical staff and encouraged athletes to participate positively in screening. In addition, screening activities built rapport between physicians and athletes and raised the profile of cardiovascular health in the organisation, which in turn provided more support for the screening program. Two principal barriers were identified: 1) when screening was conducted close to an event or tournament, this made it difficult to complete any required follow-up in time; and 2) screening junior athletes sometimes presented logistical challenges as they may only be together for a brief training camp, meaning any follow-up is completed once they return home. Discussion: Cardiac screening is implemented in unique ways in different sporting organisations to respond to their requirements. Building strong sports cardiology infrastructure, including a collaborative relationship with local cardiologists, increased the confidence of CMOs and provided a more efficient process for athletes. Key challenges to implementation were linked to the ability to adequately complete follow-up in a timely fashion. Screening should be done with an appropriate amount of time for follow-up, ideally in the off-season or sufficiently before competition. Impact/Application to the field: This study highlights the importance of developing a collaborative sports cardiology infrastructure to support an athlete cardiac screening program. Furthermore, the study emphasises the need to ensure there is sufficient time to complete required follow-up. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.